Effect of hyperglycaemia on VEGF-A splice variants, junctional integrity and vascular leakage in human feto-placental vessels from normal and type 1 diabetic pregnancies - Sciota, Flavia (2012)
Hyperglycaemia is a main feature of diabetes, and this pathology is a main complication of pregnancy. Diabetic patients often require tighter glycaemic control in pregnancy, as glucose metabolism changes, and insulin dosages need to be adjusted. Throughout gestation, the placenta is therefore subjected to periods of hyperglycaemic insult. Thus, we wished to study how brief periods of hyperglycaemia affected the feto-placental vasculature, through study of important permeability molecules, pro-permeability VEGFa, anti-permeability VEGFb, and junctional stability molecule VE-cadherin. A 15mM concentration of glucose was chosen because it is a level seen postprandially in diabetic pregnancies. We explored this by explant and perfusion methods.